Thursday
March 23, 2017

Post a New Question

Posted by on Saturday, August 17, 2013 at 6:02pm.

Solve the quadratic equation (a+b-2c)x² + (2a-b-c)x + (c+a-2b) =0 is

  • algebra - , Saturday, August 17, 2013 at 6:56pm

    -B = -2a+b+c

    B^2 = 4a^2-4ab-4ac+b^2+2bc+c^2

    -4AC = -4a^2+4ab+4ac+8b^2-20bc+8c^2
    so
    B^2-4AC=9b^2-18bc+9c^2 = 9(b^2-2bc+c^2)
    =9(b-c)^2 whew!
    sqrt(B^2-4AC) = 3(b-c) = 3b - 3c
    so
    -B+/-sqrt(B^2-4AC) = -2a+b+c +/- (3b-3c)
    = -2a+4b-2c or -2a-2b+4c
    divide those by 2A

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question